Diz Osteoartritinde alt ekstremite propriyoseptif duyusunun fiziksel fonksiyonellik üzerine etkisinin araştırılması - Mani, Ece (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
This study was performed to evaluate the lower limb proprioceptive sense (PS) in individuals with knee osteoarthritis (OA) and to analyse the relationship between PS and physical functions (PF). The study included 26 individuals with knee osteoarthritis and 26 healthy individuals. Demographical features of the individuals were recorded. The Visual Analogue Scale for Pain (VAS Pain) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC OA Index) were evaluated by subscale for pain, joint range of motion (JRM) and quadriceps (Q) angle by goniometer, PS and muscular force by isokinetic dynamometer and PF by WOMAC OA Index PF Subscale, 30-second Chair Stand Test, 40-meter Fast-Paced Walk and Stair Tests. Position senses of internal rotation and flexion of hip and ankle dorsiflexion and subtalar joint eversion kinaesthesia were worse in the individuals with knee osteoarthritis(p<0,05). Significant correlations were determined between pain and Hip and Subtalar joint PS. JRM of hip and ankle extension of the study group substantially increased in the individuals with knee OA. However, their Q angles were high (p<0,05). Meaningful correlations were found between some JRM of hip and kinaesthesia of joint. Other important correlations were specified between Joint flexion kinaesthesia of knee, JRM of inactive knee flexion, inversion position sense and JRM of inversion. Knee extensor, joint muscles of ankle/subtalar and joint muscle force of hip were lower in the individuals with knee OA. As the hip adductor and flexor of the study group increased, position sense of the joint decreased (p<0,05). Many significant relations were recorded between PS of hip and knee joint and walking and stair activities and between WOMAC OA PF subscale and position sense of subtalar joint (p<0,05). The study showed that, in comparison with the healthy individuals, PS in hip and ankle/subtalar joints was not working properly in the individuals with early knee OA. However, PS of knee joint was not affected. PS of Lower limb of the individuals with early knee OA is connected with PFs. PS impairments affected the stair activities at most. It can be seen that pain, JRM limitations, force deficiencies and changes in the orders had an impact on PS. However, there are factors which were not analysed in the study. To improve the functionality in the walking and stair activities of the individuals with knee OA, proprioceptive educations should be included in the physiotherapy program. Key Words: Pain, Muscle Force, Joint Range of Motion, Q Angle, Proprioceptive Sense, Physical Functions

Öz: Bu çalışma diz OA’lı bireylerde alt ekstremite propriyoseptif duyusunu (PD) değerlendirmek ve PD ile fiziksel fonksiyonlar (FF) arasındaki ilişkiyi incelemek amacıyla yapıldı. Çalışmaya 26 diz OA’lı ve 26 sağlıklı birey katıldı. Bireylerin demografik özellikleri kaydedildi. Ağrı Görsel Analog Skalası (GAS) ve Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC OA İndeks) ağrı alt ölçeğiyle, eklem hareket açıklıkları (EHA) ve kuadriseps (Q) açısı gonyometreyle, PD’si ve kas kuvveti izokinetik dinamometreyle ve FF’ler WOMAC OA İndeks FF Alt Ölçeği, 30 sn Sandalyeden Ayağa Kalkma, 40 m Hızlı Hızda Yürüme ve Merdiven Testleriyle değerlendirildi. Kalça internal rotasyon ve fleksiyonundaki pozisyon hisleri ile ayak bileği dorsi fleksör ve subtalar eklem eversiyon kinestezileridiz OA’lılarda daha kötüydü (p<0,05). Kalça ve subtalar eklem PD’leri ile ağrıarasında anlamlı korelasyonlar saptandı. Çalışma grubunun kalça ve diz ekstansiyon EHA’ları diz OA’lılardaanlamlı derecede azdı. Ancak Q açıları fazlaydı (p<0,05). Bazı kalça EHA’ları ile eklemin kinestezisi arasında anlamlı korelasyonlar bulundu. Diz eklem fleksiyon kinestezisiyle pasif diz fleksiyon EHA’sı ve inversiyon pozisyon duyusuyla inversiyon EHA’ları arasında anlamlıkorelasyonlar bulundu. Diz ekstansör, ayak bileği/subtalar eklem kaslarıve çoğu ölçümde kalça eklem kaslarınınkuvvetidiz OA’lılardadaha düşüktü.Çalışma grubunda kalça adduktör ve fleksör kas kuvvetleri arttıkça eklemin pozisyon hissi azaldı (p<0,05). Kalça ve diz eklem PD’leriyle yürüme ve merdiven aktiviteleri arasında, WOMAC OA FF alt ölçeğiyle subtalar eklem pozisyon hissi arasında anlamlı ilişkiler bulundu (p<0,05). Çalışma, erken evre diz OA’lılarda kalça ve ayak bileği/subtalar eklemlerdeki PD’nin sağlıklılara göre bozulduğunu göstermiştir. Ancak diz eklem PD’si etkilenmemiştir. Diz OA’lıların FF’lerinin sağlıklılardan kötü olduğu belirlenmiştir. Erken evre diz OA’lılarda alt ekstremite PD’leri FF’lerle ilişkilidir. PD bozuklukları en fazla merdiven aktivitelerini etkilemiştir. Ağrı, EHA kısıtlılıkları, kuvvet zayıflıkları ile dizilimdeki değişikliklerin PD’yi etkilediğigörülmektedir. Fakat çalışmada incelenmeyen bazı değişkenler bulunmaktadır. Diz OA’lılardayürüme ve merdiven aktivitelerinde fonksiyonelliği artırmak için propriyoseptif eğitimler fizyoterapi programına dahil edilmelidir. Anahtar Sözcükler: Ağrı, Kas kuvveti, Eklem hareket açıklığı, Q açısı, Propriyoseptif Duyu, Fiziksel Fonksiyonlar
Fizyoterapi ve Rehabilitasyon Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Sağlık Bilimleri Fakültesi, Fizyoterapi ve Rehabilitasyon Bölümü, 2016. Tez Danışmanı: Eş Tez Danışmanı: Yard. Doç. Dr. Ender Angın, Tez Danışmanı: Prof. Dr. Emine Handan Tüzün.
Keywords: Fizyoterapi ve Rehabilitasyon; Ağrı; Kas Kuvveti; Eklem Hareket Açıklığı; Q Açısı; Propriyoseptif Duyu; Fiziksel Fonksiyonlar; Pain; Muscle Force; Joint Range of Motion; Q Angle; Proprioceptive Sense; Physical Functions